Comparing the effect of combination of 1% ornidazole and 0.25% chlorhexidine gluconate (Ornigreat™) gel and Aloe Vera gel in the treatment of chronic periodontitis: A randomized, single-blind, split-mouth study - Gautami Subhadra Penmetsa; Bukkapatnam Subbareddy; Anudeep Mopidevi; P Arunbhupathi; Vivek Baipalli; Sudharani Pitta (Wolters Kluwer Medknow Publications, 2019)
Aim and Objective: The aim of this study is to compare the efficiency of subgingivally delivered 1% ornidazole and 0.25% chlorhexidine (CHX) gluconate (Ornigreat™ gel) and Aloe vera (AV) gel in the treatment of chronic periodontitis. Materials and Methods: Twenty chronic periodontitis patients with pocket depths ranging from 4 to 6 mm bilaterally at least in one site were included in the study. After a thorough nonsurgical periodontal therapy, 1% ornidazole and 0.25% CHX gluconate (Ornigreat™ gel) and AV gel were subgingivally delivered into the pocket sites, and the clinical parameters such as plaque index (PI), gingival index (GI), bleeding index (BI), and clinical attachment level (CAL) were evaluated at baseline and after 4 weeks. Results: In both the groups, a reduction in PI, GI, and probing depth readings was evidenced after 4 weeks. A significant improvement was noticed in the BI in the AV group when compared with that of Ornigreat™ group. Taking CAL into consideration, though improvement was there in both the groups, it was not appreciable. Conclusion: AV which is an herbal derivative when subgingivally delivered in the pocket site could be an equally effective and affordable substitute for Ornigreat™ gel.